2023
DOI: 10.1590/s1677-5538.ibju.2023.0348
|View full text |Cite
|
Sign up to set email alerts
|

"Single-Surgeon" versus "Dual-Surgeon" Robot-Assisted Radical Prostatectomy and Pelvic Lymph-nodes Dissection: Comparative Analysis of Perioperative Outcomes

Riccardo Bertolo,
Marco Carilli,
Michele Antonucci
et al.

Abstract: Purpose: To compare the perioperative outcomes of robot-assisted radical prostatectomy (RARP) with pelvic lymph-nodes dissection (PLND) when the same surgeon performs RARP and PLND versus one surgeon performs RARP and another surgeon performs PLND. Materials and Methods: From January 2022 to March 2023, data of consecutive patients who underwent RARP with PLND were prospectively collected. The surgeries were performed by two "young" surgeons with detailed profi le. Specifi cally for the study purpose, one surg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Dr. Bertolo and collegues from Italy performed on page 732 ( 6 ) a nice comparative analysis of perioperative outcomes about "Single-Surgeon" versus "Dual-Surgeon" in Robot-Assisted Radical Prostatectomy (RARP) and Pelvic Lymph-nodes Dissection (PLND) and concluded that when RARP and PLND are split onto two surgeons, the operative time is shorter by 20 minutes compared to when a single surgeon performs RARP and PLND.…”
mentioning
confidence: 99%
“…Dr. Bertolo and collegues from Italy performed on page 732 ( 6 ) a nice comparative analysis of perioperative outcomes about "Single-Surgeon" versus "Dual-Surgeon" in Robot-Assisted Radical Prostatectomy (RARP) and Pelvic Lymph-nodes Dissection (PLND) and concluded that when RARP and PLND are split onto two surgeons, the operative time is shorter by 20 minutes compared to when a single surgeon performs RARP and PLND.…”
mentioning
confidence: 99%